A Study on the Effect of Difficult Parent Behaviour on the Teachers’ Work: Exploring the Impact of Difficult Parent Behaviour on Teachers' Work and Well-being (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The researcher was interested in studying the school teachers’ effectiveness in dealing with difficult parents and their reported negative feelings while they interfaced them. For this purpose there were 252 school teachers who responded on the Parent Stress Questionnaire. Analysis included descriptive information, factor analysis and intercorrelation. Factor analysis indicated that the problematic behaviors could “affect” the teachers’ pleasure in working and their relationship with the parents. Finding impressed that teachers’ effectives and negative feelings were reported as ‘moderate’ while dealing with difficult parent.